2004
DOI: 10.1111/j.1365-2044.2004.03460.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of esmolol on the dose of propofol required for induction of anaesthesia*

Abstract: SummaryCardiac output may be an important determinant of the induction dose of intravenous anaesthetic. Esmolol is known to reduce cardiac output, and we examined its effect on the propofol dose required for induction of anaesthesia. The size of the effect seen with esmolol was compared with midazolam co-induction. Sixty patients were randomly allocated to placebo (saline), esmolol (1mg.kg )1 bolus, followed by an infusion at 250 lg.kg) or midazolam (0.04 mg.kg )1 ) groups. Induction of anaesthesia commenced 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
0
31
0
2
Order By: Relevance
“…Upton et al 6 reported that the initial arterial concentration of propofol after a short infusion was inversely related to CO in sheep. 15 No investigations, however, have assessed the influence of changing CO on propofol concentrations during constant rate infusion in humans. Epidural anesthesia has been reported as exerting no influence on the pharmacokinetics of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Upton et al 6 reported that the initial arterial concentration of propofol after a short infusion was inversely related to CO in sheep. 15 No investigations, however, have assessed the influence of changing CO on propofol concentrations during constant rate infusion in humans. Epidural anesthesia has been reported as exerting no influence on the pharmacokinetics of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…Although further studies exploring the detailed mechanism are needed, these data suggest a potential role of β 1 -adrenoreceptors in spinal nociceptive processing. [1][2][3][4] In addition, the sedative properties of these compounds may decrease anesthetic requirements [5][6][7][8] and reduce bispectral index, a value reflecting activity of the cerebral cortex and levels of consciousness. 3 In recent years, there have been several reports identifying the antinociceptive and analgesic effects of β 1 -blockers in both animal and human studies.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The advantages of using landiolol in clinical anesthesia include that it is very short-acting and highly selective for β 1 receptors, 11 thus rendering easy titration and less side effects such as asthma or peripheral vasoconstriction compared to other longer-acting β blockers. As landiolol is metabolized very quickly by serum pseudochorinesterase and carboxyesterase in the liver to an inactive metabolite with a short half-life, it is reasonable to assume that most of the intrathecal landiolol will undergo decomposition and excretion before the drug diffuses into the blood and takes systemic pharmacological effect.…”
Section: Discussionmentioning
confidence: 99%
“…They compared effect of esmolol addition on propofol and 60% N2O requirements and observed that esmolol significantly decreases requirements for both agents 5 . In two different studies Topçu and colleagues and Wilson and colleagues reported esmolol decreased both propofol and remifentanil requirements 30,31 .…”
Section: Figure 2 Comparison Of Pre and Postoperative Cortisol Levelsmentioning
confidence: 99%